Pengaruh Influencer Marketing Terhadap Purchase Intention Dengan Brand Attitude Sebagai Variabel Mediasi Pada Richeese Factory Di Garut - Hilman Rismanto; Akmal Husna; Andini Agistiani; Ai Heni Sari; Wina Andrianti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the influence of influencer marketing on purchase intention, with brand attitude as a mediating variable, at Richeese Factory in Garut.. The uniqueness of this research lies in the integration of influencer marketing and purchase intention within a single research framework, positioning brand attitude as the mechanism for indirect influence. This study employs a quantitative approach using descriptive and associative methods. Data collection was carried out using questionnaires as the primary data source, supported by secondary data. The research sample consists of 96 respondents aged 17–35 years who are active on social media and have been exposed to Richeese Factory's influencer marketing campaigns, determined using the Lemeshow formula. Data analysis was performed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The findings reveal that influencer marketing does not have a direct effect on purchase intention but exerts a positive and significant impact on brand attitude. Furthermore, brand attitude is proven to have a positive and significant effect on purchase intention and acts as a mediator in the relationship between influencer marketing and consumers' purchase intention. These findings underscore the importance of fostering a positive brand attitude to enhance the effectiveness of influencer marketing strategies.